Dances in the Name of the Dead: Syarga and Ghyapri/Klepri Rituals Among Gurungs - Gurung, Shanti (Social Inquiry: Journal of Social Science Research, 2022)
Within the diversified and multicultural country like Nepal, there are many death rituals depending on the basis of their caste, religion, geographical area and their economic status. The Gurungs have their own kind of death rituals termed as Arghu (pae), in principle, appears to have similar purpose with the annual Shraddha as practices by the Brahmin-Chhetri and other people. The entitled research topic explores about the death rituals syarga and klepri dances to be performed differently during the pae. The ritual of Arghum among the Gurungs is a three-day event which includes the dancing rituals of Syarga and Klepri together with prayers and rituals that aim to send the deceased person’s soul to heaven. Main purpose of this study is to findout how the Gurungs believe their death ritual by dancing and its soul connection to the deceased. The paper follows the interpretative approach to present the story of the special dances and rituals performed in the name of the dead by her/his relatives, friends and fellow villagers. This study was conducted among the gurungs of Gorkha district. Seven death rituals were carried out for the field study where five klepri gurus and 5syarga dancer was taken as respondent. My own participation in and observations of the ritual performances, and activities supplemented by my interview with elderly and knowledgeable people including ritual specialists has yielded the essential data needed to learn about how Gurung people understand human life and the relations between themselves and their deceased ancestors. Main finding of this study is dance in the name of deceased which believes that dance is one of the important part for human life and it’s fluctuations. As same like gurung people believe that we can dance in the name of the dead which reminiscences the previous life where she/he belong to.